2022
DOI: 10.7554/elife.76075
|View full text |Cite
|
Sign up to set email alerts
|

Control of nuclear size by osmotic forces in Schizosaccharomyces pombe

Abstract: The size of the nucleus scales robustly with cell size so that the nuclear-to-cell volume ratio (N/C ratio) is maintained during cell growth in many cell types. The mechanism responsible for this scaling remains mysterious. Previous studies have established that the N/C ratio is not determined by DNA amount but is instead influenced by factors such as nuclear envelope mechanics and nuclear transport. Here, we developed a quantitative model for nuclear size control based upon colloid osmotic pressure and tested… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
78
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 102 publications
(193 reference statements)
15
78
1
Order By: Relevance
“…1d, Methods). MSD analysis showed that GEM particle motion in the cytoplasm was largely diffusive (MSD ≈ Dτ), following a robust power law with apparent diffusivity D app,100ms = 0.3 ± 2*10 -3 µm 2 /sec (AVG ± CI) and anomalous diffusion exponent ⍺ = 0.92 ± 5*10 -3 (AVG ± CI), which were similar to previously published measurements in fission yeast (Lemière et al, 2021;Molines et al, 2022). The diffusivity of the 40 nm GEMs in the cytoplasm was roughly 40 times slower than the theoretical prediction for simple Stokes-Einstein diffusion in water -and corresponded to the particle's expected diffusion rate in a 75% glycerol solution in water.…”
Section: Statistical Characterization Of Cytoplasmic Gem Particle Dif...supporting
confidence: 87%
See 2 more Smart Citations
“…1d, Methods). MSD analysis showed that GEM particle motion in the cytoplasm was largely diffusive (MSD ≈ Dτ), following a robust power law with apparent diffusivity D app,100ms = 0.3 ± 2*10 -3 µm 2 /sec (AVG ± CI) and anomalous diffusion exponent ⍺ = 0.92 ± 5*10 -3 (AVG ± CI), which were similar to previously published measurements in fission yeast (Lemière et al, 2021;Molines et al, 2022). The diffusivity of the 40 nm GEMs in the cytoplasm was roughly 40 times slower than the theoretical prediction for simple Stokes-Einstein diffusion in water -and corresponded to the particle's expected diffusion rate in a 75% glycerol solution in water.…”
Section: Statistical Characterization Of Cytoplasmic Gem Particle Dif...supporting
confidence: 87%
“…To reduce environmental variability, these unicellular cells were grown at 30 °C under optimal conditions in shaking liquid cultures to exponential growth phase and mounted in imaging chambers with fixed dimensions under constant temperature and imaged acutely. Using variable angle epifluorescence microscopy (VAEM) (Delarue et al, 2018;Konopka and Bednarek, 2008;Lemière et al, 2021;Molines et al, 2022) we tracked GEM particle motion at 100 Hz for 10 s, as described previously (Delarue et al, 2018;Lemière et al, 2021;Molines et al, 2022) (Fig. 1a-b, Methods).…”
Section: Statistical Characterization Of Cytoplasmic Gem Particle Dif...mentioning
confidence: 99%
See 1 more Smart Citation
“…We estimate it to be at most less than 10% compared to a tensionless nucleus for the upper bounds of the realistic values for the constitutive tension and the cytoskeletal compressive forces. As a consequence, we find that the nuclear size changes predicted by the bag-in-a-bag model (Deviri and Safran, 2021;Lemière et al, 2021) in presence of changes in external forces are at odds with our experimental observations in cell spreading and detachment experiments. During cell spreading, the cytoskeleton is believed to apply compressive forces to the nucleus, which, would lead to volume-decreasing deformations, in contrast with the observed increase in volume.…”
Section: Estimates Of Relevant Parameterscontrasting
confidence: 46%
“…The key ingredient of the model is the assumption that osmotic pressure plays a primary role in setting nuclear and cytoplasmic volume . We use a bag in a bag model, similar to refs (Deviri and Safran, 2021; Lemière et al, 2021). Following these studies, we assume a spherical cell and nucleus, and that on the obervation time scales both the cell surface and the nuclear surface are at mechanical equilibrium (Salbreux et al, 2007;Venkova et al, 2021).…”
Section: Model Ingredientsmentioning
confidence: 99%